THE EFFECTIVENESS OF USING TIME TOKEN (TT) MODEL TO IMPROVE STUDENTS SPEAKING SKILL AT VII GRADE MTs SWASTA NURUL ISLAMACADEMIC YEARS 2023/2024 - Elvi Hilda Jayanti; SabrunJamil; Putri Ayumi (Tuwah Pande: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
A Thesis English Education Department the Faculty of Teachers Training and Education, stkip us Kutacane.The aim of the research was to find out The Effectiveness of Using Time Token (TT) Model To Improve Student Speaking Skills at VII grade MTs Swasta Nurul Islam Academic Year 2023-2024. The population of this study consists of all 25 students in Class VII, with a sample size of 25 students. The research method employed is an experimental method with a one-group pretest and posttest design, and data analysis using the "t" test. The initial test results show that students had an average score of 46.8, categorized as less satisfactory, with a standard deviation of 6.14. There was an improvement in the final test scores, with an average score of 78.28, categorized as good, and a standard deviation of 5.41. Based on the initial and final test results, and considering the passing grade (KKM) for English in high school is 70, Improve Student Speaking Skills is classified as good. The hypothesis testing yields a t-value of 17.20, compared with the t-table value at a 5% significance level (1.711). As a result, the hypothesis is accepted (17,20> 1.711)In conclusion, there The Effectiveness of Using Time Token (TT) Model To Improve Student Speaking Skills at VII grade MTs Swasta Nurul Islam Academic Year 2023-2024.